FAKTOR DETERMINAN JUMLAH KONSUMSI SOFT DRINK PER HARI PADA ANAK USIA 10-12 TAHUN DI PEDESAAN - Dewi, Clara Rashinta; Subagio, Hertanto Wahyu; Panunggal, Binar (Departemen Ilmu Gizi, Fakultas Kedokteran, Universitas Diponegoro, 2017)
Background: Children become consumer target of soft drink. Many factors influencing children’s consumption of soft drink. There are only few studies about factor influencing children’s consumption in rural area. Objective : To analyze total soft drink consumption per day among 10-12 year-old children in rural area and analyze determinant factors of soft drink consumption.Methods : Cross-sectional study design in 109 children aged 10-12 years who was selected by consecutive sampling. Data collected were gender, nutrition knowledge related soft drink, attitude to soft drink consumption,, pocket money, peer influence, and exposure to mass media. The instruments used are questionnaire and Semi Quantitative Food Frequency Questionaire (SQ-FFQ). Data were analyze using rank Spearman test and Chi Square test.Result : Total soft drink consumption per day was 422,0±483,94ml. Variables that correlated with total soft drink consumption per day were gender (p=0,025), attitude to soft drink consumption (r=0,28;p=0,003) and peer influence (r=0,25;p=0,007). Variables that are not correlated with total soft drink consumption per day were nutrition knowledge (r=-0,10;p=0,269), pocket money (r=-0,10;p=0,265), exposure to mass media (r=0,15;p=0,116).Conclusion : Factors that correlated with total soft drink consumption per day were gender (p=0,025), attitude to soft drink consumption (r=0,28;p=0,003) and peer influence (r=0,25;p=0,007).